Enhancement on the tribological properties of 316L stainless steel via boron and alumina additions using mechanical alloying and powder metallurgy techniques - Macit, Cevher Kursat; Aksakal, Bunyamin; Horlu, Merve (Elsevier Sci Ltd, 2025)
This study investigates the effects of boron (B) and alumina (Al2O3) additions on the microstructural evolution, hardness, and tribological performance of 316L stainless steel matrix composites. The composites were fabricated via mechanical alloying (MA) followed by powder metallurgy (PM) sintering at 1150 degrees C under an argon atmosphere. Five compositions were produced: unreinforced 316L, mono-reinforced with 5 wt% B or 5 wt% Al2O3, and hybrid-reinforced variants containing 2.5-5 wt.% of both reinforcements. X-ray diffraction (XRD) analysis confirmed the formation of intermetallic boride phases such as Fe2B and FeB in B-containing samples, while Al2O3 preserved its thermally stable alpha-corundum structure. SEM-EDX analysis revealed a homogeneous dispersion of reinforcements, especially in hybrid samples, with limited agglomeration. Relative density decreased with increasing reinforcement content, reaching a minimum of 90.5 % in the 316L-5B-5Al2O3 sample due to enhanced porosity. Hardness results showed a substantial increase in reinforced samples compared to the base alloy (150 +/- 4 HV). The highest hardness (265 +/- 5 HV) was achieved in the hybrid composite, reflecting a 76.7 % improvement attributed to dispersion and transformation strengthening effects. Wear tests conducted at room temperature and 500 degrees C under dry sliding conditions revealed that the hybrid composite exhibited the lowest wear rates: 4.61 x 10- 8 mm3/Nm (RT) and 6.54 x 10- 8 mm3/Nm (500 degrees C), indicating wear reductions of approximately 89.5 % and 91.7 %, respectively, compared to unreinforced 316L. The coefficient of friction (COF) also decreased significantly from 0.53665 (316L) to 0.21 (RT) and 0.22 (500 degrees C) in the hybrid sample, due to the formation of lubricious oxide layers and mechanically stable wear surfaces. The synergistic effects of B and Al2O3 reinforcements significantly enhanced mechanical properties and high-temperature wear resistance, demonstrating the potential of these hybrid composites for advanced structural applications under severe operating conditions.
Keywords: Mechanical alloying; Powder metallurgy; Hybrid composite; 316L stainless steel; Tribology